Potential of phase change materials and their effective use in solar thermal applications: A critical review. (25th January 2023) - Goel, Varun; Saxena, Abhishek; Kumar, Muneesh; Thakur, Akshay; Sharma, Akshay; Bianco, Vincenzo
Highlights: Different PCMs operated solar thermal systems are studied for performance enhancement. Thermo-physical properties of a PCM are the key factors for its selection. Complete charging & discharging of a PCM is essential for its complete life cycle. Cost effectiveness is a major issue for adoption of a PCM for solar thermal systems. Assessment of different PCMs is further required for their technology readiness level. Abstract: Potential of the thermal energy storage materials especially phase change materials (PCM) is great support to the thermal systems for their performance enhancement especially for those systems which are operated on solar energy. In the present review study, some PCM operated solar thermal systems have been studied thoroughly to observe the real behavior of their improved performance by using a specific phase change material under variable ambient conditions. Apart from this, it has been observed that a complete charging and discharging cycle is necessary for a specified life cycle of the tested PCM. Heat transfer studies of different solar applications which operates on a variety of phase change materials shows that the performance improvement is fairly possible if the PCM is selected by considering the thermodynamic behavior of 'to be used' thermal system under a specific environment. It helps in selecting a suitable phase change material for a specific solar energy application. Results of the review study recommends some suitable phase change materials for solar cookers, solar stills, solar ponds, air heaters, PV systems and water heaters on the basis of their thermal characteristics specially operating temperature and their costs. A brief study on technology readiness level and levelized cost of storage shows the appropriateness of phase change materials for a wide adoption of them to be used in solar thermal applications. Overall, this study provides a very useful information about the thermal behavior, selection and the possible use of different phase change materials in solar energy systems, round the globe.